2022
DOI: 10.48075/amb.v4i2.30324
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação diagnóstica da presença de resíduos de agrotóxicos em amostras de urina de moradores de uma “vila rural” do município de Francisco Beltrão/PR

Abstract: A contaminação por agrotóxicos em comunidades rurais é um problema mundialmente conhecido, mas, geralmente, ocultado. O desenvolvimento de pesquisas que identifiquem este tipo de contaminação é fundamental para se avançar no debate sobre os efeitos deletérios dos agrotóxicos. Este artigo, apresenta os resultados de uma pesquisa que investigou os níveis de resíduos de agrotóxicos em amostras de urina de moradores de uma vila rural localizada no município de Francisco Beltrão/PR. Segundo relato dos moradores, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Other studies have indicated the presence of glyphosate in the human body. In South America, Candiotto et al [ 32 ] detected glyphosate-AMPA in 90% of urine samples collected from residents of a rural village in the Southern region of Brazil who were exposed to pesticide drift from the spraying of neighboring crops. Other researchers have recently detected the active ingredient in urine samples in North America [ 33 , 34 ], Europe [ 35 , 36 ], Asia [ 37 ], Oceania [ 38 ], and Africa [ 39 ].…”
Section: Glyphosate Usementioning
confidence: 99%
“…Other studies have indicated the presence of glyphosate in the human body. In South America, Candiotto et al [ 32 ] detected glyphosate-AMPA in 90% of urine samples collected from residents of a rural village in the Southern region of Brazil who were exposed to pesticide drift from the spraying of neighboring crops. Other researchers have recently detected the active ingredient in urine samples in North America [ 33 , 34 ], Europe [ 35 , 36 ], Asia [ 37 ], Oceania [ 38 ], and Africa [ 39 ].…”
Section: Glyphosate Usementioning
confidence: 99%